Combustion of Argemone mexicana biodiesel blends in a constant-volume DICI engine. Issue 4 (4th July 2019) - Parida, M. K.; Rout, A. K.
ABSTRACT: Argemone mexicana methyl ester, prepared by a transesterification process, was tested for combustion analysis with variation of blends and loads at a fixed compression ratio of 17.5. Maximum cylinder pressure was obtained for a 40% blend due to longer combustion duration. The combustion parameter net heat release rate and cumulative heat release rate increase with engine load. The net heat release rate decreases and cumulative heat release rate increases with an increase in the percentage of biodiesel. The crank angle position corresponding to maximum pressure shifts away with an increase in the proportion of biodiesel. The maximum pressure rise rate is highest for diesel and its occurrence is advanced with loading and percentage of biodiesel. Combustion duration decreases with engine loading and increases with concentration.